2007
DOI: 10.1002/ardp.200600160
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Cytotoxicity Evaluation of Novel Naphthindolizinedione Derivatives

Abstract: Novel 6,11-dioxo-6,11-dihydro-benzo[f]pyrido[1,2-a]indole-12-carboxamide derivatives and the corresponding 7,10-dihydroxy analogues were designed in accordance with Moore's and Pindur's theory and synthesized based on the structural similarity with known antitumour agents such as ellipticine, daunorubicin, mitoxantrone and 9-aminoacridine-4 carboxamide derivatives. These compounds, including structural variations of the amide side chain, were evaluated in the NCI panel of human tumour cell lines, from which 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In addition, the relevant role of the amide chain in improving the effect is also proved by the data reported by Cheng et al [4] against this cell line (GI 50 in the range 1 -12 lM) for compound 1 and for the N,N-syn and N,N-anti analogues with an acetyl or a nitrile group in the place of the ethoxycarbonyl unit of the regioisomers 2 and 3. Finally, the important role of the amide chain was expected by comparison of the values for amide 4 [7] with ethyl ester 1, both on the non small cell lung A549/ ATCC [1] and on leukaemia HL60 (TB) lines [4] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the relevant role of the amide chain in improving the effect is also proved by the data reported by Cheng et al [4] against this cell line (GI 50 in the range 1 -12 lM) for compound 1 and for the N,N-syn and N,N-anti analogues with an acetyl or a nitrile group in the place of the ethoxycarbonyl unit of the regioisomers 2 and 3. Finally, the important role of the amide chain was expected by comparison of the values for amide 4 [7] with ethyl ester 1, both on the non small cell lung A549/ ATCC [1] and on leukaemia HL60 (TB) lines [4] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the structural similarity with known antitumor agents such as ellipticine, daunorubicin, mitoxantrone, and derivatives of DACA (= N-[2-(dimethylamino)ethyl]acridine-4-carboxamide), we have recently [7] designed and synthesized a series of analogues of ester 1. These compounds were evaluated in the NCI panel of human tumor cell lines, from which the N,N-dimethylethylamino chain (as in compound 4) turned out to be the most relevant structural modification to induce the highest activity and selectivity towards leukaemia, colon, and renal cancer cell lines with GI 50 values from lower than 10 nM to 0.2 lM [7].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 5-7 were synthesized by a nucleophilic substitution of norfloxacin (1) on the suitable quinones 2-4 [12,13] in dichloromethane solution at room temperature in the presence of triethylamine (Scheme 1). The products were easily isolated with yields in the range 70-87%.…”
Section: Resultsmentioning
confidence: 99%
“…Further investigation has indicated that IQDs are a novel type of TOP1 catalytic inhibitor, which can specifically inhibit the DNA cleavage activity of TOP1, and induce cancer cell cycle arrest at the G2/M phase. [10] Therefore, it is worthy to further study the biological property of IQD-type compounds. Preliminary structure-activity relationship (SAR) assessment indicated that the existence of nitrogen in the A ring of IQDs is essential for their cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%